Performance Assessment of Agrotourism Oriented Irrigation Systems in Subak Sembung, Denpasar City - Agripina, I Gusti Ayu Widi; Siswoyo, Hari; Sumiyati, Sumiyati (Universitas Jember, 2023)
Subak Sembung has a wide coverage area of 103 ha of rice fields with a total length of 5.1 km of tertiary irrigation canals. The Subak Sembung area has experienced land conversion of 14 ha which has had an impact on the performance of the subak system. The strategy that can be implemented to maintain the sustainability of the subak system is to develop agrotourism. Based on the survey results at the study area, there are several problems that have the potential to disrupt the performance of the irrigation system, including damage to irrigation structures and leakage of irrigation canals, and a lack of support for subak development towards agrotourism. The aim of this study was to assess the condition and performance of an agrotourism-oriented irrigation system in Subak Sembung. This research was conducted using field survey and interview methods. Field surveys were carried out with the aim of determining the conditions of agrotourism-oriented irrigation systems. Interviews were conducted to assess the performance of an agrotourism oriented irrigation system using the subak assessment form based on the Tri Hita Karana developed by the Udayana University Subak Unit and the agro-tourism form. Based on the research that has been done, it can be stated that the condition of the agrotourism oriented irrigation system in Subak Sembung is good. This is shown based on the functioning of irrigation network assets and non-irrigation networks. The performance of agrotourism oriented irrigation systems in Subak Sembung is in the range of 3.66 - 5.00 in the good category.